Lipid Composition of Egg Yolk and Serum in Laying Hens Fed Diets Containing Black Cumin (Nigella sativa) - El Bagir, Nabiela M.; Hama, Aziza Y.; Hamed, Rania M.; El Rahim, Ahmed G. Abd; Beynen, Anton C. (International Journal of Poultry Science, 2006)
Laying hens were fed diets without or with 10 or 30 g of the whole seed of black cumin (Nigella sativa)/kg. The concentrations of total lipids, total cholesterol, phospholipids and triacylglycerols in serum and egg yolk were measured. Feeding of the diets with 1 and 3% black cumin seeds for a period of three months reduced egg yolk total cholesterol by 34 and 42%, respectively. Serum cholesterol concentrations averaged for the whole feeding period were lowered by 15 and 23% after feeding the diets with 1 and 3% black cumin seeds, respectively. Black cumin seeds in the diet of laying hens also caused a lowering of serum and egg-yolk concentrations of triacylglycerols and phospholipids. Inclusion of black cumin seeds in the diet caused a significant reduction in egg production, without any effect on egg width and length, while there was a significant increase in hen`s body weight. The increase in body weight in the hens fed black cumin seeds is explained by the ingested feed energy not used for egg production. It is concluded that black cumin seeds and/or the active principle are of interest as potential egg-yolk cholesterol-lowering agents.